Analisis Sistem Pengendalian Intern Penerimaan Dan Pengeluaran Kas Pada Koperasi Unit Desa Rahmat Tani (RATA) - M P A. Rozak Barus; Kamilah kamilah (CERED Indonesia Institute, 2022)
The results of this study are (1). The Internal Control System in the Rahmat Tani Village Unit Cooperative (RATA) has been carried out quite well, because almost all activities are in accordance with the main elements of the internal control system described. However, there are several elements that still need to be improved. (2) The internal control components in the Rahmat Tani Village Unit Cooperative (KUD) (RATA) are good. And in accordance with the COSO (The Committee Of Sponsoring Organizations) guidelines. (3). The cash receipt and disbursement system in the Rahmat Tani Village Unit Cooperative (RATA) is quite organized because the procedures and steps in it are reliable. This also applies to each unit business in the Village Unit Cooperative (KUD) Rahmat Tani.